Religion, families, and health : population-based research in the United States - Hummer, Robert A. (New Brunswick, N.J. : Rutgers University Press, 2010)
This book is a compilation of population-based research on the relationships of religion to family life and health.
Introduction / Christopher G. Ellison and Robert A. Hummer -- Religion and family life outcomes -- Religion and the timing of first births in the United States / Lisa D. Pearce -- Religion and child rearing / Duane F. Alwin and Jacob L. Felson -- Religion and adolescent sexual behavior / Mark D. Regnerus -- The influence of religion on ties between the generations / Valarie King -- Religion and family values reconsidered : gender traditionalism among conservative protestants / John P. Bartkowski and Xiaohe Xu -- From generation to generation : religious involvement and attitudes toward family and pro-family outcomes among U.S. Catholics / Amy M. Burdette and Teresa A. Sullivan -- Religious intermarriage and conversion in the United States : patterns and changes over time / Linda J. Waite and Alisa C. Lewin -- Childhood religious denomination and early adult asset accumulation / Lisa A. Keister -- Religious affiliation and participation as determinants of women's educational attainment and wages / Evelyn Lehrer -- Religion, family, and women's employment among Muslim and Christian Arab Americans / Jennan Ghazal Read -- Religion and health outcomes -- Religion and depressive symptoms in late life / Neal Krause -- Religion and physical health among U.S. adults / Marc A. Musick and Meredith G. F. Worthen -- Religious involvement and mortality risk among pre-retirement aged U.S. adults / Robert A. Hummer ... [et al.] -- Religious attendance and cause-specific mortality in the United States / Richard G. Rogers, Patrick M. Krueger, and Robert A. Hummer -- Race, religious involvement, and health : the case of African Americans / Christopher G. Ellison ... [et al.] -- Jewish identity and self-reported health / Isaac W. Eberstein and Kathleen M. Heyman -- Religion, sexually risky behavior, and reproductive health : the Mormon case / Tim B. Heaton -- Religion and the new immigrants : impact on health behaviors and access to health care / Helen Rose Ebaugh -- Looking ahead -- The religious demography of the United States : dynamics of affiliation, participation, and belief / Darren E. Sherkat -- Future directions in population-based research on religion, family life, and health in the United States / Christopher G. Ellison and Robert A. Hummer.
Includes bibliographical references and index.
Keywords: United States -- Religion; Medicine -- United States; Families -- United States; Religion -- United States; Health Behavior -- United States